2020
DOI: 10.3390/d12040154
|View full text |Cite
|
Sign up to set email alerts
|

Species Richness, Ecology, and Prediction of Orchids in Central Europe: Local-Scale Study

Abstract: Orchids are one of the most species-rich families in the world, and many species are under threat in numerous countries. Biodiversity research focusing on the relationship between the richness of orchid species and ecological factors was performed across the Cerová vrchovina Mts (Western Carpathians) testing impact of 26 explanatory variables. We aimed to determine the main ecological predictors controlling species richness and to predict potential species richness patterns. Altogether, 19 orchid species were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
5
2
0
Order By: Relevance
“…These were mainly species of Cephalanthera longifolia , Cephalanthera rubra and Anacamptis morio . The authors [ 6 ], who carried out similar research in the Western Carpathians (Cerová vrchovina Mountains), the closest to our territory, confirmed that calcium geological substrates were an important factor, which in their case were important driving forces of orchid species diversity. They confirmed the results of previous studies, which identified carbonates and their soils as the most important substrates for the occurrence of terrestrial orchids [ 14 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…These were mainly species of Cephalanthera longifolia , Cephalanthera rubra and Anacamptis morio . The authors [ 6 ], who carried out similar research in the Western Carpathians (Cerová vrchovina Mountains), the closest to our territory, confirmed that calcium geological substrates were an important factor, which in their case were important driving forces of orchid species diversity. They confirmed the results of previous studies, which identified carbonates and their soils as the most important substrates for the occurrence of terrestrial orchids [ 14 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 61%
“…Research carried out in the Slovak Republic and other countries confirms that significant factors of distribution are the geological conditions of the area, which has a considerable impact on their occurrence and overall phytogeographical distribution of these species, as well as indicative values of populations, their communities and spatio-temporal changes in occurrence; these claims can be defined on the basis of the relationship to the environment and the influence of environmental factors. Similar research has been carried out in the Western Carpathians [ 6 ] and in Europe by several authors [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionsupporting
confidence: 66%
“…On the other hand, this is possibly because soil conditions can promote or inhibit the seed germination rate of orchid species [67,68]. Furthermore, exchangeable calcium ion (Ca 2+ ex ) has a significant influence on orchid species distribution (Figure 9E), which coincides with the findings of Hrivnák et al [69] and the essential role of calcium ions in pollen germination and pollen tube growth [70].…”
Section: Relationships Between Environmental Factors and The Distribution Of Brachypetalum Orchids In Southwest Chinasupporting
confidence: 85%
“…Third, the environmental conditions that affect the distribution of orchid species are relatively well known and include climatic variables (e.g. annual temperature and precipitation), soil and land use variables, and elevation (Djordjević et al, 2016;Evans & Jacquemyn, 2020;Hrivnák et al, 2020;Pfeifer et al, 2009;Štípková et al, 2022;Tsiftsis et al, 2011Tsiftsis et al, , 2019Tsiftsis & Djordjević, 2020).…”
Section: Introductionmentioning
confidence: 99%